2011
DOI: 10.1007/s12070-011-0398-0
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Case of Dystrophic Calcification in Masseter: A Diagnostic Challenge

Abstract: The objective of this study was to present an unusual case of isolated dystrophic calcification in masseter and the diagnostic challenge it posed. A case report on a 14-year-old boy presented with swelling in left parotid region along with the review of literature was reported. Histopathological and biochemical analyses of the excised mass diagnosed this affliction as dystrophic calcification. Dystrophic calcification is deposition of calcium salt in degenerated tissues in the presence of normal calcium and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Several case reportsdescribe extra-parotid dystrophic calcification in the parotidomasseteric region. Naik et al reported several intramasseteric dystrophic calcifications in a 14-year-old boy, and in their report they highlight the pre-operative diagnostic challenge, including a nondiagnostic FNA [5]. Sencimen et al reported two small intramasseteric calcifications, and Mohiuddin et al reported a collection of supramasseteric dystrophic calcified nodules [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Several case reportsdescribe extra-parotid dystrophic calcification in the parotidomasseteric region. Naik et al reported several intramasseteric dystrophic calcifications in a 14-year-old boy, and in their report they highlight the pre-operative diagnostic challenge, including a nondiagnostic FNA [5]. Sencimen et al reported two small intramasseteric calcifications, and Mohiuddin et al reported a collection of supramasseteric dystrophic calcified nodules [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…There is a variety of conditions that may cause abnormal calcification in various tissues. It may have some connection with abnormal calcium phosphate metabolism as seen in metastatic calcifications [ 6 ]. However, dystrophic calcification is deposition of calcium salt in degenerated tissues related to normal calcium and phosphorous metabolism [ 7 ].…”
Section: Case Presentationmentioning
confidence: 99%
“…Currently, there is no established protocol for its treatment. Some clinicians have recommended observation, but others have suggested the surgical treatment case by case [ 6 ]. This article presents a rare case of the multiple dystrophic calcifications in the masseter muscle.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory disorders, such as scleroderma, dermatomyositis and systemic lupus erythematosus may result in dystrophic calcification. Dystrophic calcification has been reported at various sites by multiple researchers but the commonest site is heart muscle and valves [5,6]. Dystrophic calcification involving skeletal muscle, such as masseter muscle, pterygoid muscle, and anterior compartment of the leg has also been reported [7][8][9].…”
Section: Case Reportmentioning
confidence: 99%